The Future of Remote Work: Responses to the Pandemic - Mark, Gloria; Rintel, Sean; Kun, Andrew L.; Sellen, Abigail (Human-Computer Interaction, 2022)
Introduction to the Special Issue of Human-Computer Interaction. The goal of this special issue on The New Future of Work is to provide a forum to explore where we have come from and to suggest future directions if we are to meet these challenges. This issue showcases timely and novel research on currently disrupted or evolving work practices that can enable us to reflect on how past findings shed light on our current situation, to help us prepare for a world in which work may be done very differently. The idea for this special issue began with the Microsoft 2020 New Future of Work Symposium. This Symposium was held in August 2020, with 245 attendees, representing researchers and practitioners from industry, academia, and government, all working in interdisciplinary fields. Participants convened together for three days of keynotes, talks, and productive conversations. The discussions were exciting, ranging from presenting new designs for technology to support team awareness, introducing ways to increase motivation and productivity in a work-from-home context, and introducing novel interventions to preserve team identity in remote work environments. These conversations were provocative and raised significant questions, as well as providing pathways to solutions.